Precipitation chemistry and wet deposition in a remote wet savanna site in West Africa: Djougou (Benin) - (:unkn) unknown (My University, 2015)
In the framework of the IDAF (IGAC/DEBITS/AFrica) international program, this study aims to study the chemical composition of precipitation and associated wet deposition at the rural site of Djougou in Benin, representative of a West and Central African wet savanna. Five hundred and thirty rainfall samples were collected at Djougou, Benin, from July 2005 to December 2009 to provide a unique database. The chemical composition of precipitation was analyzed for inorganic (Ca2+, Mg2+, Na+, , K+, , Cl−, ) and organic (HCOO−, CH3COO−, C2H5COO−, C2O42−) ions, using ion chromatography. The 530 collected rain events represent a total of 5706.1 mm of rainfall compared to the measured pluviometry 6138.9 mm, indicating that the collection efficiency is about 93%. The order of total annual loading rates for soluble cations is > Ca2+ > Mg2+ > K+. For soluble anions the order of loading is carbonates > HCOO− > > CH3COO− > > Cl− > C2O42− > C2H5COO−. In the wet savanna of Djougou, 86% of the measured pH values range between 4.7 and 5.7 with a median pH of 5.19, corresponding to a VWM (Volume Weighed Mean) H+ concentration of 6.46 μeq·L−1. This acidity results from a mixture of mineral and organic acids. The annual sea salt contribution was computed for K+, Mg2+, Ca2+ and and represents 4.2% of K+, 41% of Mg2+, 1.3% of Ca2+, and 7.4% of . These results show that K+, Ca2+, , and Mg2+ were mainly of non-marine origin. The marine contribution is estimated at 9%. The results of the chemical composition of rainwater of Djougou indicates that, except for the carbonates, ammonium has the highest VWM concentration (14.3 μeq·L−1) and nitrate concentration is 8.2 μeq·L−1. The distribution of monthly VWM concentration for all ions is computed and shows the highest values during the dry season, comparing to the wet season. Identified nitrogenous compound sources (NOx and NH3) ar
Keywords: African Research